Perception of grammatical tone in Akan patients with left and right hemisphere brain damage. - Tsiwah, Frank; Popov, Srdjan; Bastiaanse, Roelien (Clinical Linguistics & Phonetics, 2024)
It remains a matter of debate what roles the left and right hemispheres play in processing speech prosody. Brain lesion studies have demonstrated that lexical tone perception among native speakers of tonal languages is more disrupted in left hemisphere damaged (LHD) individuals than right hemisphere damaged (RHD) individuals. This has been taken to suggest that linguistically-relevant prosodic cues are predominantly left-lateralised, whereas non-linguistic stimuli are predominantly right-lateralised. However, this phenomenon has only been examined in lexical tone, leaving grammatical tone perception unexplored. The aim of this study was twofold: Firstly, to examine how individuals with LHD and RHD perceive grammatical tone, and secondly to compare grammatical tone to non-linguistic tone perception. Therefore, native Akan speakers with LHD, RHD and no-brain damage (NBD) controls were tested in two discrimination tasks that examined linguistic and non-linguistic tone perception. The results showed that while both the individuals with LHD and RHD show impairment in grammatical tone perception, there was a trend of a better performance for the RHD group. Nonetheless, for non-linguistic tone perception, individuals with LHD outperformed the RHD individuals, although both had reduced performance compared to the NBD individuals. A further analysis revealed that the reduced perceptual abilities of both the LHD and RHD groups in grammatical tone perception can be attributed to grammatical problems rather than tone per se. We conclude that there is potentially a bilateral involvement of the two hemispheres in grammatical tone processing, with the left being the dominant hemisphere.